O processo de avaliação da aprendizagem na Educação Infantil no município de Humaitá-AM - Silva, Jéssica Freitas (Brasil, 2021)
The research presented here comes from the Group of Studies and Research in Early Childhood Education - GPEDIN, linked to the National Council for Scientific and Technological Development -CNPq and the Federal University of Amazonas (UFAM), through the research project "Child Education: policies and practices”. The present work aims to analyze the evaluation process in public Early Childhood Education institutions in the municipality of Humaitá, in southern Amazonas. In Early Childhood Education, assessment is related to the monitoring of the child, through interactions and experiences in the educational space (HOFFMANN, 2012; KRAMER, 2011; MICARELLO, 2010) Thus, we see the need to better understand this dynamic in the spaces of Early Childhood Education. The research approach is qualitative, of the case study type. Analysis of documents and reports, the application of a questionnaire and dialogues with the teachers of Early Childhood Education were carried out. We identified that institutions use different assessment instruments to monitor the development of children's learning and that the dialogues produced in training activities are important. Teachers understand that the experiences in these spaces are enriching and the need for the child's active participation.